Strengthening Integrated Financial Crime Enforcement in Indonesia: Evaluating the Institutional Synergy Between the Financial Services Authority (OJK) and the Indonesian Financial Intelligence Unit (PPATK) - Farhan Fathur Rahman; Indah Sari Br. Barus; Qori Asvifah Bintang; Rafly Alikhsan Sikumbang (ISNU Sumatera Utara, 2026)
The rapid transformation of the banking sector through digital financial services has significantly increased the complexity of banking crimes, extending beyond conventional fraud to sophisticated forms of financial misconduct, including cyber-enabled banking fraud, cross-border money laundering, beneficial ownership concealment, and illicit financial flows. These developments have challenged the effectiveness of traditional banking supervision and criminal law enforcement mechanisms. This study aims to critically examine the institutional relationship between the Financial Services Authority (Otoritas Jasa Keuangan/OJK) and the Indonesian Financial Transaction Reports and Analysis Center (Pusat Pelaporan dan Analisis Transaksi Keuangan/PPATK) in combating banking crimes under the Indonesian legal framework. Employing normative legal research, this study applies statutory, conceptual, analytical, and comparative approaches by examining Indonesian banking legislation alongside international standards concerning financial supervision and anti-money laundering issued by the Financial Action Task Force (FATF) and other international institutions. The findings demonstrate that although OJK and PPATK possess distinct legal mandates, the effectiveness of banking crime enforcement largely depends on institutional coordination rather than individual institutional authority. OJK performs prudential regulation and supervisory functions aimed at preventing systemic risks and ensuring regulatory compliance within the banking sector, whereas PPATK functions as Indonesia's Financial Intelligence Unit (FIU) responsible for collecting, analyzing, and disseminating financial intelligence associated with suspicious financial transactions. Nevertheless, overlapping supervisory responsibilities, fragmented regulatory coordination, delayed information exchange, and the absence of an integrated financial crime governance mechanism continue to impede effective law enforcement. This study proposes an Integrated Financial Crime Enforcement Model that emphasizes real-time institutional coordination, regulatory harmonization, intelligence-based supervision, and collaborative asset recovery as strategic measures to strengthen Indonesia's financial integrity. The proposed model contributes to the development of banking law by integrating prudential supervision and financial intelligence into a comprehensive institutional framework capable of responding to increasingly sophisticated financial crimes.